Comparing the Effect of Traditional Educational Model and Game-Based Learning Approach on Self-Efficacy in Adolescent Boys - Rezaei , Meysam; Ebrahimi Khayat, Elnaz; Farokhi, Armin; Najafian Razavi, Mahdi (Health Nexus, 2025)
This study aimed to compare the effects of the traditional educational model and the Game-Based Learning (GBL) approach on self-efficacy in adolescent boys. A quasi-experimental design was used with a pre-test and post-test model. Thirty male students aged 10 to 13 years from Mashhad were selected using convenience sampling and randomly assigned to two groups: one receiving traditional instruction and the other exposed to GBL. Self-efficacy was measured using the Self-Efficacy Questionnaire for Children and Adolescents (SEQ-C). The intervention spanned eight weeks, with the traditional group focusing on teacher-led, structured activities, while the GBL group engaged in interactive, game-based tasks designed to enhance cognitive and emotional skills. Data were analyzed using descriptive statistics and ANCOVA to evaluate differences between groups. The results revealed that the GBL approach significantly improved self-efficacy compared to the traditional educational model. Participants in the GBL group exhibited a larger mean increase in self-efficacy scores (M = 19.52) compared to the traditional group (M = 6.86). ANCOVA confirmed the effectiveness of GBL, with a large effect size (\u03b72 = 0.80). These findings align with previous studies emphasizing the role of interactive and engaging learning environments in fostering self-efficacy. Game-Based Learning proved to be a more effective approach than traditional instruction in enhancing self-efficacy among adolescent boys. These findings highlight the potential of GBL as a transformative educational strategy, particularly for fostering confidence, motivation, and autonomy in students. Future research should explore long-term effects and applicability across diverse populations.